Macroeconomics : principles and practice / Bruce Littleboy; John B Taylor; Akila Weerapana - Littleboy, Bruce, 1956-
Macroeconomics: Principles and Practice offers students concepts, intuition and understanding, supported by an 'Economist's toolkit'. This Toolkit consolidates appendix-style material into one section to show in a simple manner how calculations and models are used in the real world. This edition follows the same intuitive modular approach as the last and includes guidelines for instructors who prefer alternative, more traditional sequencing. Microeconomics concepts are explored throughout the text where needed, such as when reference is made to 'supply and demand'. New chapters present macroeconomic theory more intuitively. Policy debates are explained in depth but in a simple and more modern way. The focus is on understanding concepts in a realistic context